2016
DOI: 10.2169/internalmedicine.55.6448
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Tuberculosis from a Pulmonary Latent Tuberculosis Infection during Antiviral Triple Therapy for Chronic Hepatitis C

Abstract: A 62-year-old man was diagnosed with the onset of tuberculosis (Tb) from a pulmonary latent tuberculosis infection (LTBI) during triple therapy with pegylated interferon α2a, ribavirin, and telaprevir for a chronic hepatitis C infection in 2013 before interferon (IFN)-free anti-viral therapy was introduced in Japan. A liver biopsy before IFN treatment revealed the presence of epithelioid cell granulomas (ECGs). IFN may also be employed for chronic hepatitis B infection and malignant tumors, thus, special atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In addition, a partial loss-of-function polymorphism in the type I IFN receptor (IFNAR1) is associated with resistance to TB in humans 21 . A small number of cases also link IFN treatment during chronic viral infections with increased susceptibility to TB 6,7,[22][23][24] . In addition, numerous animal studies have demonstrated causal roles for type I IFNs in susceptibility to Mtb 6,7,9,15,16,[25][26][27] and other bacterial infections 18,28 .…”
mentioning
confidence: 99%
“…In addition, a partial loss-of-function polymorphism in the type I IFN receptor (IFNAR1) is associated with resistance to TB in humans 21 . A small number of cases also link IFN treatment during chronic viral infections with increased susceptibility to TB 6,7,[22][23][24] . In addition, numerous animal studies have demonstrated causal roles for type I IFNs in susceptibility to Mtb 6,7,9,15,16,[25][26][27] and other bacterial infections 18,28 .…”
mentioning
confidence: 99%
“…Several clinical studies have reported reactivation of tuberculosis in patients undergoing IFN-α based therapy for chronic viral hepatitis ( Sabbatani et al, 2006 ; Farah and Awad, 2007 ; Telesca et al, 2007 ; Belkahla et al, 2010 ; Guardigni et al, 2012 ; Abutidze et al, 2016 ; de Oliveira Uehara et al, 2016 ; Matsuoka et al, 2016 ). In addition, a very recent study showed that impaired type I IFN signaling due to a rare East Asian functional mutation in the IFNAR1 gene was associated with increased resistance to tuberculosis ( Zhang et al, 2018 ).…”
Section: Type I Ifn–inducible Transcriptional Signature In Human Tubementioning
confidence: 99%
“…All studies found a positive influence of adjuvant T1-IFN therapy on clinical outcomes in active TB (4549). Conversely, IFN-α treatment without concomitant antibiotic treatment, e.g., for hepatitis C, has been described to cause reactivation of latent TB (5057). While reactivation of latent TB and treatment of active TB are two distinct clinical situations, the latter finding suggests an unfavorable role for T1-IFNs in TB pathogenesis.…”
Section: T1-ifns In Tbmentioning
confidence: 99%
“…However, case reports of TB reactivation under IFN-α treatment without concomitant antibiotics have put T1-IFNs in a negative spotlight (5057). Furthermore, a T1-IFN transcriptional signature in circulating leukocytes is associated with active TB.…”
Section: T1-ifns In Tbmentioning
confidence: 99%
See 1 more Smart Citation